Irrigation and dryland fruit production: opportunities and constraints faced by small-scale farmers in Venda - Robbertse, P.J. (Petrus Johannes), 1932- (University of Pretoria, 2013)
Dissertation (M Inst Agrar (Plant Production: Horticulture))--University of Pretoria, 2007.